Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1995
DOI: 10.1115/95-gt-355
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Experimental/Computational Study of Flow in Turbine Blade Cooling Passage: Part I — Experimental Study

Abstract: A combined experimental/computational study has been performed for flow in a rotating serpentine passage which approximates the internal cooling passage for turbine blades. Experimental results are presented in Part I and computational results, in Part II. Benchmark quality velocity measurements were acquired by laser-Doppler velocimetry at Reynolds number of 25,000 and Rotation number of 0.24. The results were used to assess the influence of the Coriolis force on the velocity characteristics and to explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The geometry of that problem is the same as that studied here except for the absence of ribs. For that problem, the computed Nusselt numbers on the leading and trailing walls for the up-leg part of the U-duct were compared with measured one by Wagner, et al (1991a). Those comparisons, described in Stephens,et al (I 996b), showed that very good agreements were obtained.…”
Section: Numerical Methods Of Solutionmentioning
confidence: 97%
See 2 more Smart Citations
“…The geometry of that problem is the same as that studied here except for the absence of ribs. For that problem, the computed Nusselt numbers on the leading and trailing walls for the up-leg part of the U-duct were compared with measured one by Wagner, et al (1991a). Those comparisons, described in Stephens,et al (I 996b), showed that very good agreements were obtained.…”
Section: Numerical Methods Of Solutionmentioning
confidence: 97%
“…Wagner, et al (1991a,b), Morris & Salemi (1992), Han, et al (1994), and Cheah, et al (1996) investigated rotating ducts with smooth walls. Taslim, et al (1991), Wagner, et al (1992), Zhang, et al (1993), Johnson, et al (1994), Zhang, et al (1995), Tse (1995), and Kuo & Hwang (1996) reported studies on rotating ducts with ribbed walls. These investigators studied the effects of Reynolds number (Re), rotation number (Ro), and a buoyancy parameter that accounts for the coolant-to-wall temperature ratio, rotational speed, and the radial position of the coolant duct relative to the axis of rotation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such measurements have been reported by Tse and Steuber (1997), Tse et al (1994), Iacovides et al (1998), Hsieh et al (1997), Bons and Kerrebrock (1998) and Servouze (1998). However, these flow measurements have all been made with the instrumentation on the stationary frame, and only provide conditionally sampled data.…”
Section: / Flow and Heat Transfer In Rotating Channelsmentioning
confidence: 99%
“…Tse et al (1994), Tse and McGrath (1995), and McGrath and Tse (1995) measured the local velocity distributions in a rotating serpentine channel with smooth walls, and compared their experimental results with distributions that were predicted numerically by solving the relevant governing conservation equations with a Navier-Stokes code by Rhie (1986). Other recent numerical studies on turbulent flow and heat transfer in rotating smooth channels include Prakash and Zerkle (1992) and .…”
Section: Introductionmentioning
confidence: 99%